(untitled) (Journal of Pathology of Nepal, 2021)
Background: Cell blocks are micro biopsies and are complimentary to cytology smears and give a = more accurate diagnosis. This study aimed to study cell block as an adjunct for FNAC smears in intra- abdominal lesions, and to compare the sensitivity and specificity of the cell block with FNACs of intra- abdominal lesions. Materials and Methods: This study was done for three years. FNAC of the intra- abdominal lesions were done and smears were prepared for routine staining (HE, PAP, and MGG), the rest of the material was submitted in 60% ethanol for cell block preparation. Results: FNACs were done in 102 cases, cell blocks were obtained in 95 cases, and histopathological correlation in 87 cases. The maximum number of cases was between 51-60 years age group. The liver was the most common organ involved with 22 cases(21.56%). Nonneoplastic cases were 17, neoplastic was 85. Statistical analysis was done for benign and malignant cases. Histopathological correlations were available in 71 neoplastic cases. The sensitivity, specificity PPV, NPV, and diagnostic accuracy of combined FNACs and Cell blocks were 98.27%, 100%, 100%, 92.85%, and 98.59% respectively. Conclusions: FNAC of intra-abdominal lesions is a safe, simple, cost-effective procedure and along with cell blocks gives a precise diagnosis. They can also be used for histochemical stains, immuno- cytochemistry, and in-situ-hybridization.